Результати економічного районування галузі промислового садівництва зони степу України: сучасні реалії - Колокольчикова, Ірина Володимирівна; Колокольчикова, Ирина Владимировна; Kolokolchykova, Iryna (My University, 2019)
UK: У роботі пропонується оцінка результатів застосування економічного районування як наукового методу територіальної організації галузі промислового садівництва на прикладі зони Степу України. Метод зональної спеціалізації розглядається як визначення багатьох критеріїв щодо успішного розвитку галузі садівництва з урахуванням природно-ресурсного потенціалу зон, а також характеристик плодово-ягідних порід. Відправною точкою аналізу є показник масштабів територіального розміщення багаторічних плодових насаджень по зонах України, їх кількісна та якісна характеристики. Співвідношення площ насаджень по областях і зонах, їх сортовий склад визначає зональність і приналежність до відповідної природної зони. Проводиться оцінка результатів районування зони Степу за показником площ багаторічних насаджень та порівняння з рекомендаціями Галузевих програм. Порівняльний аналіз показників проходить за видами плодових і ягідних культур у розрізі їх структури. У цілому пропонується об’єктивна оцінка розвитку галузі промислового садівництва в зоні Степу і Півдні України для аналізу сучасних реалій та виявлення резервів розвитку цього процесу. RU: В работе предлагается оценка результатов применения экономического районирования как научного метода территориальной организации отрасли промышленного садоводства на примере зоны Степи Украины. Метод зональной специализации рассматривается как определение многих критериев успешного развития отрасли садоводства с учетом природно-ресурсного потенциала зон, а также характеристик плодово-ягодных пород. Отправной точкой анализа является показатель масштабов территориального размещения многолетних плодовых насаждений по зонам Украины, их количественная и качественная характеристики. Соотношение площадей насаждений по областям и зонам, а также их сортовой состав подчеркивают форму зональности и принадлежности к соответствующей природной зоне. Проведена оценка результатов районирования зоны Степи по показателю площадей многолетних насаждений и в сравнении с рекомендациями Отраслевых программ. Сравнительный анализ показателей проходит по видам плодовых и ягодных культур в разрезе их структуры. В целом предлагается объективная оценка развития отрасли промышленного садоводства в зоне Степи и на Юге Украины для анализа современных реалий и выявления резервов развития этого процесса. EN: The paper proposes an assessment of the results of applying economic zoning as a scientific method of the territorial organization of the industrial gardening industry using the example of the Steppe zone of Ukraine. The method of zonal specialization is considered as the determination of many criteria for the successful development of the horticultural industry, taking into account the natural resource potential of zones, as well as the characteristics of fruit and berry species. The starting point of the analysis is an indicator of the scale of territorial distribution of perennial fruit plantations in the zones of Ukraine, their quantitative and qualitative characteristics. The ratio of the areas of plantings on areas and zones, and also their varietal structure thereby emphasizes the form of zonality and belonging to the corresponding natural zone. This affiliation lays the Foundation for successful business in this industry both in terms of productivity and economic efficiency. The author assesses the results of zoning of the Steppe zone in terms of the area of perennial plantations and in comparison with the recommendations of the Sectoral programs. The current development of the fruit industry does not fully reflect the recommendations. The steppe zone is not disclosed as much as possible in the production of fruits and berries, which means that the natural resource potential is not fully disclosed. Only for some fruit crops, such as sweet cherries and peaches, land-use indicators are acceptable. That is, in general, an objective assessment of the development of the industrial gardening industry in the Steppe zone and the South of Ukraine is offered in order to analyze the current realities and identify the reserves for the development of this process. Identification of weaknesses and detailed study of opportunities will allow analyzing the development of zoning in the industry of industrial horticulture from simple to complex.
Результаты экономического районирования отрасли промышленного садоводства зоны Степи Украины: современные реалии
The results of the economic zoning of industrial gardening of the zone of the Steppe of Ukraine: modern realities
Keywords: економічне районування; природно-ресурсний потенціал; природні зони; промислове садівництво; багаторічні насадження; экономическое районирование; природно-ресурсный потенциал; природные зоны; промышленное садоводство; многолетние насаждения; economic zoning; natural resource potential; natural territories; industrial fruit growing; perennial plantings